Molecular characterization of a novel reassortment Mammalian orthoreovirus type 2 isolated from a Florida white-tailed deer fawn - Ahasan, Mohammad Shamim; Subramaniam, Kuttichantran; Sayler, Katherine A.; Loeb, Julia C.; Popov, Vsevolod L.; Lednicky, John A.; Wisely, Samantha M.; Campos Krauer, Juan M.; Waltzek, Thomas B. (Virus research, 2019)
•First report of a Mammalian orthoreovirus (MRV) in a cervid host.•The white-tailed deer reovirus was genetically determined to be a type 2 MRV (MRV2).•The MRV2 may have resulted from the reassortment of MRVs originating from multiple wildlife species. Mammalian orthoreovirus (MRV) is the type species of the genus Orthoreovirus and causes a range of significant respiratory, nervous or enteric diseases in humans and animals. In 2016 a farmed white-tailed deer (Odocoileus virginianus) fawn became ill, displaying clinical signs of lethargy, dehydration, and profuse foul-smelling diarrhea. A necropsy was performed after the three-week-old fawn died and various tissue samples were submitted to the University of Florida’s Cervidae Health Research Initiative for diagnostic evaluation. Aliquots of homogenized heart, liver, and spleen tissues were inoculated onto Vero E6 cells. After virus-specific cytopathic effects (CPE) were detected in Vero cells inoculated with spleen homogenate, infected cells were fixed in glutaraldehyde and analyzed by transmission electron microscopy (TEM), which revealed icosahedral virus particles approximately 75 nm in diameter with morphologies consistent with those of reoviruses within the cytoplasm of the infected cells. RNA extracted from virions in the spent media of infected cells with advanced CPE was used to prepare a cDNA library, which was sequenced using an Illumina MiSeq sequencer. Complete coding sequences for ten separate reovirus segments were attained, and these indicated the isolated agent was a MRV. Genetic and phylogenetic analyses based on the outer capsid sigma-1 (σ1) protein gene sequences supported the Florida white-tailed fawn isolate as a type 2 MRV that branched as the sister group to a MRV-2 strain previously characterized from the urine of a moribund lion (Panthera leo) in Japan. However, analyses based on 7/10 genes (L1-L2, M2-M3, S2-S4) supported the white-tailed deer MRV as the closest relative to a type 3 MRV strain isolated from a dead mink in China. These data suggest the white-tailed deer MRV may have resulted from the natural reassortment of MRVs originating from multiple wildlife species. To our knowledge, this is the first detection of MRV-2 infection in a white-tailed deer. Continued surveillance efforts are needed to determine whether this MRV-2 strain poses a health threat to farmed white-tailed deer populations.